Réponses

2013-08-14T23:34:13+02:00

   A  =  (x + 5)² − (2x − 1)² + (3x + 4) (x − 1)

       =  (x² + 10x + 25) − (4x² − 4x + 1) + (3x² − 3x + 4x − 4)

       =  x² + 10x + 25 − 4x² + 4x − 1 + 3x² − 3x + 4x − 4

       =  x² − 4x² + 3x² + 10x + 4x − 3x + 4x + 25 − 1 − 4

       =  15x + 20

 

  Donc             A  =  0

 

   si       15x + 20  =  0

 

  soit si         15x  =  − 20

 

 d'où si             x  =  −20/15

 

 donc si            x  =  −4/3

 

 

    [Vérification :  A(−4/3)  =  (−4/3 + 5)² − (2 × −4/3 − 1)² + (3 × −4/3 + 4) (−4/3 − 1)

                                      =  (−11/3)² − (−11/3)² + (0) (−7/3)

                                      =  121/9 − 121/9 + 0

                                      =  0]